Finite element modelling of thin intermetallic compound layer fractures - Ooi Eang Pang; Ruslizam Daud; Nasrul Amri Mohd Amin; Mohd Afendi Rojan; Mohd Shukry Abd Majid (Journal of Mechanical Engineering and Sciences, 2017)
A thin intermetallic compound (IMC) of solder ball joint induces strong stress concentration between the pad and solder where a crack propagated near the IMC layer. The fracture mechanism of the IMC layer is complex due to the effect of IMC thickness, crack length, solder thickness and Young’s Modulus. At present, there is still an undefined exact geometrical model correlation for numerical simulations of IMC layer fracture. Thus, this paper aims to determine the accuracy of IMC layer models subjected to crack-to-width length ratio (a/W) in correlation with the ASTM E399-83 Srawley compact specimen model using finite element (FE) analysis. Several FE models with different geometrical configurations have been proposed under 10 MPa tensile loading. In this study, the two dimensional linear elastic displacement extrapolation method (DEM) is formulated to calculate the stress intensity factor (SIF) at the crack tip. The study showed that with an error of 0.58% to 0.59%, a width of 2.1 mm and a height of 1.47 mm can be recommended as the best geometrical model for IMC layer fracture modelling which provides a wider range for a/W from 0.45 to 0.85 instead of from 0.45 to 0.55. This result is significant as it presents a method for determining fracture parameters at thin IMC layers with a combination of singular elements with meshes at different densities which is tailored to the Srawley model.